Implementasi Buku Saku Pendidikan Ramah Anak sebagai Media Penyuluhan Pendidikan Keluarga - Khoiriyah, Hafidhatul; Wahyuni, Sri; Zulkarnain, Zulkarnain (Journal of Nonformal Education and Community Empowerment, 2018)
This research aims to describe the functionality and absorption of matter child friendly education pocket book (Kuku Perak) as media of counseling family education. The research done with the type of descriptive quantitative. The data collection method used is the questionnaires with Likert scale, multiple choice test and documents study. Analysis of the data used is the percentage formula and frequency distribution. The results of research Kuku Perak is it can be implemented as a media of counseling family education or parenting education.